2017
DOI: 10.1038/nature23663
|View full text |Cite|
|
Sign up to set email alerts
|

Lhx6-positive GABA-releasing neurons of the zona incerta promote sleep

Abstract: Multiple populations of wake-promoting neurons have been characterized in mammals, but few sleep-promoting neurons have been identified1. Wake-promoting cell types include hypocretin and GABA (γ-aminobutyric-acid)-releasing neurons of the lateral hypothalamus, which promote the transition to wakefulness from non-rapid eye movement (NREM) and rapid eye movement (REM) sleep2,3. Here we show that a subset of GABAergic neurons in the mouse ventral zona incerta, which express the LIM homeodomain factor Lhx6 and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
220
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(227 citation statements)
references
References 41 publications
7
220
0
Order By: Relevance
“…For retrograde monosynaptic tracing, i.e., labeling neurons directly presynaptic to a defined population, the original rabies virus -based system (Wickersham et al, 2007b) has been refined in ways that range from improvements in the complementing helper viruses (Kim et al, 2016; Kohara et al, 2014; Liu et al, 2017; Miyamichi et al, 2013; Wall et al, 2010) to the use of a rabies virus strain with reduced toxicity (Reardon et al, 2016) and the addition of a destabilization domain to the viral nucleoprotein (Ciabatti et al, 2017). Although there are fewer tools available, anterograde monosynaptic tracing – i.e., labeling neurons directly postsynaptic to a starting population – based on the vesicular stomatitis virus or herpes simplex virus has been described (Beier et al, 2011; Zeng et al, 2017).…”
Section: Anatomy and Connectivitymentioning
confidence: 99%
“…For retrograde monosynaptic tracing, i.e., labeling neurons directly presynaptic to a defined population, the original rabies virus -based system (Wickersham et al, 2007b) has been refined in ways that range from improvements in the complementing helper viruses (Kim et al, 2016; Kohara et al, 2014; Liu et al, 2017; Miyamichi et al, 2013; Wall et al, 2010) to the use of a rabies virus strain with reduced toxicity (Reardon et al, 2016) and the addition of a destabilization domain to the viral nucleoprotein (Ciabatti et al, 2017). Although there are fewer tools available, anterograde monosynaptic tracing – i.e., labeling neurons directly postsynaptic to a starting population – based on the vesicular stomatitis virus or herpes simplex virus has been described (Beier et al, 2011; Zeng et al, 2017).…”
Section: Anatomy and Connectivitymentioning
confidence: 99%
“…These datasets have been used as the basis for genetic studies that selectively disrupt development of specific hypothalamic regions and/or cell types (20)(21)(22)(23)(24), leading in some cases to identification of novel functions for previously characterized hypothalamic regions or cell types (25,26). However, these datasets have important limitations: they do not provide cellular resolution of gene expression data, and they do not efficiently measure coexpression of multiple genes.…”
mentioning
confidence: 99%
“…Here we present results of our titration experiments to test the effects of using different dilutions of the helper viruses, to show the reasons for the specific concentrations that we recommend. We found that the two-helper combination described above and in Liu et al [18] gives much better results than the simpler single AAV which we described earlier [16], which did not allow independent optimization of transsynaptic tracing efficiency and minimization of background labeling in Cre-negative mice. We also found that excessively high titers of the helper viruses gave very poor results, suggesting that preventing toxicity due to overly high expression of the helper virus genes is as important as ensuring sufficient expression of them.…”
Section: Introductionmentioning
confidence: 74%
“…Having previously found Addgene's Viral Service (www.addgene.org/viral-service/aav-prep) to be an excellent source of high-quality AAVs, we authorized them to package and distribute three of our published Cre-dependent helper AAVs: the standalone helper virus AAV-syn-FLEX-splitTVA-EGFP-B19G from Kohara et al [16] (referred to below as the "tricistronic" helper virus) and the two viruses to be used in combination as described in Liu et al [18]: AAV-syn-FLEX-splitTVA-EGFP-tTA and AAV-TREtight-mTagBFP2-B19G. Although the resulting preparations, all with serotype 1 capsids, had much higher titers than earlier batches that we had previously used successfully for similar experiments, we nonetheless first tried using them "straight": undiluted except insofar as, for the two-helper-virus combination, the two viruses were combined in a 50/50 mixture by volume (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation